2001
DOI: 10.1103/physrevb.63.174107
|View full text |Cite
|
Sign up to set email alerts
|

Fermi surface incommensurate nestings and phase equilibria in Cu-Pd alloys

Abstract: The Cu-Pd phase diagram shows two low-temperature ordered phases corresponding to B2 and L1 2 superlattices or, regardless of the site occupation, to bcc and fcc geometrical arrangements. We show how the phase equilibria between these intermetallic compounds can be understood by introducing a hypothetical bcc random-alloy phase and a three-step transformation from B2 to random bcc to random fcc to L1 2 . The two order-disorder transformations, B2 to random bcc and random fcc to L1 2 , analyzed in the framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
5
14
0
Order By: Relevance
“…There are many reasons for such a fortune: as it has been already pointed out, the CPA allows for a very careful determination of spectral properties 2 and Fermi surfaces. 3 However, for the arguments discussed in the present paper, two other aspects of the CPA are particularly amenable: its simple and elegant formulation 4 in terms of the multiple scattering theory 5 and the fact that, since it clearly defines a homogeneous meanfield alloy, it constitutes a natural starting point for perturbative studies of the fluctuations. The last feature has allowed the development of successful methods for the study of phase equilibria 6 and magnetic phenomena 7 in metallic alloys and led to surprisingly accurate calculations of properties connected with typical Fermi liquid effects, such as spin 8 and concentration waves.…”
Section: Introductionmentioning
confidence: 99%
“…There are many reasons for such a fortune: as it has been already pointed out, the CPA allows for a very careful determination of spectral properties 2 and Fermi surfaces. 3 However, for the arguments discussed in the present paper, two other aspects of the CPA are particularly amenable: its simple and elegant formulation 4 in terms of the multiple scattering theory 5 and the fact that, since it clearly defines a homogeneous meanfield alloy, it constitutes a natural starting point for perturbative studies of the fluctuations. The last feature has allowed the development of successful methods for the study of phase equilibria 6 and magnetic phenomena 7 in metallic alloys and led to surprisingly accurate calculations of properties connected with typical Fermi liquid effects, such as spin 8 and concentration waves.…”
Section: Introductionmentioning
confidence: 99%
“…One system that has been extensively studied is Cu 12x Pd x (see [5] for phase diagram), where the nesting is thought to be particularly strong. Below T c ͑ϳ800 K͒, this system adopts either the B2 or L1 2 long-range ordered structure or one of a wealth of long period superstructures, depending on composition (see, for example, [6,7]).…”
mentioning
confidence: 99%
“…Full details of these studies of the Fermi surfaces can be found in Ref. 52 and a comparison with experiment in Ref. 20.…”
Section: Resultsmentioning
confidence: 99%